Information in the COVID-19 Pandemic Era: Is it Fact Fake or Fear - Mohamed Mliless; Mohammed Larouz (Vivid: Journal of Language and Literature, 2021)
Concerns about fake news on social network sites are ascending. The aim is to deliberately create and share false or manipulated information to mislead the public, to cause harm for public figures, and/or get financial gains.  In Morocco, the rise of fake news in the COVID-19 era highlights the fight of many media institutions, including the Maghreb Agency Press, against misinformation. The content used by media and social network sites to report about the spread of the disease has put the pandemic at the forefront of people’s daily discourse. Actually, the outbreak of unfiltered information on the COVID-19 contagion seems to have sparked fear amongst the public via re-tweetable tweets, likable posts, and shared documents. For about three months, a deluge of fake news was created to target COVID-19, health stuff, society, security, and religion, among other public domains. Relying on the Maghreb Agency Press database fact-checking, the present study investigated news stories, verified by the agency as false stories, since the outbreak of COVID-19 in the country between March 11 and June 11th, 2020. The data comprise 249 stories posted, shared, and re-tweeted by people on social network sites. Overall, an increasing trend in sharing fake news on COVID-19, health, security, crime, society, and education, among other issues has been observed. The role of social media is determinant in the propagation of misinformation. Equally important, the constructed and shared content on social networking sites regarding the issue of COVID-19 needs to be carefully considered so as not to maximize public fear and panic.